Repercussion of the University of the older in Cienfuegos. Course 2005-2006. - Tania Goicochea Borrell (Medisur)
The University of the older is a great opportunity in life for the retired. The need of achieving a preparation of our aged citizens and to try to make them feel useful in the society, has made possible the existence of classrooms in different places, which offer a determined program that allows the extension of knowledge of these students. In the present work, a brief exposition is made about the results of this program in the province of Cienfuegos.